Meniscal biology in health and disease. (4th May 2017) - Cook, James L.; Kuroki, Keiichi; Stoker, Aaron M.; Monibi, Farrah A.; Roller, Brandon L.
ABSTRACT: The knee is a fascinating yet complex joint. Researchers and clinicians agree that the joint is an organ comprised of highly specialized intrinsic and extrinsic tissues contributing to both health and disease. Key to the function and movement of the knee are the menisci, exquisite fibrocartilage structures that are critical structures for maintaining biological and biomechanical integrity of the joint. The biological/physiological functions of the menisci must be understood at the tissue, cellular and even molecular levels in order to determine clinically relevant methods for assessing it and influencing it. By investigating normal and pathological functions at the basic science level, we can begin to translate data to patients. The objective of this article is to provide an overview of this translational pathway so that progression toward improved diagnostic, preventative, and therapeutic strategies can be effectively pursued. We have thoroughly examined the pathobiological, biomarker, and imaging aspects of meniscus research. This translational approach can be effective toward optimal diagnosis, prevention, and treatment for the millions of patients who suffer from meniscal disorders each year.